Ética católica e cultura do trabalho : uma reflexão sobre a imigração italiana no Estado do Espírito Santo - Pereira, Flavia Salles Nunes (2011)
The main purpose of this research is to comprehend the role played by Catholic Church in the determination of an immigration policy to Brazil and the role in the development of an ideal immigrant model that could be manipulated to expand and consolidate t